Implementasi Kebijakan Pengembangan Koleksi Dinas Perpustakaan dan Kearsipan Provinsi Kalimantan Timur. - Andi Anwar; Andi Sri Yusnani; Nur Azizah; Enos Paselle (Jurnal Syntax Admiration, 2024)
The purpose of this study was to describe the collection development policy implemented at the East Kalimantan Provincial Library and Archives Office. In this study the authors took a qualitative approach using descriptive methods, namely collecting data through library research and field research through interviews, observation and collection of documents related to the problem and analyzing data inductively. This research was conducted at the Library and Archives Office of East Kalimantan Province, Jl. Ir. H. Juanda No. 4 Samarinda East Kalimantan. Researchers applied interactive data analysis techniques which include data reduction, data display, and verification. The results of the study showed that the Regional Library and Archives Office of East Kalimantan Province in carrying out collection development has not been fully achieved. This is due to limited manpower and cooperation in handling the collection development process. The collection development process is in the form of adding collections, namely; purchases, gifts and deposits. The collection development process includes six activity components consisting of community analysis, selection policy, selection, procurement and weeding of collections and collection evaluation.